Production Behavior in Sharia Economy: in the Perspective of Maqashidi Interpretation - Atabik, Ahmad (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
In the perspective of sharia economy, production activities are linked to humans and their participation in economic activities. The problem is, then, how the Qur'an views production behavior as processing resources into outputs in order to increase public interests (maslahah) for humankind. This paper focuses on the study on how to picture the concept of production behavior in sharia economy, as understood through the contemporary commentary approach called maqashidi interpretation. This study is a literature research based on a review of texts related to economic recession with a focus on maqashidi interpretation. According to the results of this study, several terms are used to refer to the term 'production' in the Quran, such as 'amal, sina'ah, and other terms mentioned in the verses of the Quran in general. Maqashidi interpretation on production behavior seeks to comprehend the verses referring to production based on public interest values for those working, creating, and manufacturing products. In relation to the maqasid verses of the Quran, production behavior leads to human needs which encompass five preservations, such as preserving religion (hifz al-din), soul (hifz al-nafs), minds and creativity (hifz al-'aql), property and materials (hifz al-mal), and continuity of heredity (hifz al-nasl), all of which aim to benefit Muslims.